The US Food and Drug Administration Sentinel System: a national resource for a learning health system. (12th September 2022) - Brown, Jeffrey S; Mendelsohn, Aaron B; Nam, Young Hee; Maro, Judith C; Cocoros, Noelle M; Rodriguez-Watson, Carla; Lockhart, Catherine M; Platt, Richard; Ball, Robert; Dal Pan, Gerald J; Toh, Sengwee
Abstract: The US Food and Drug Administration (FDA) created the Sentinel System in response to a requirement in the FDA Amendments Act of 2007 that the agency establish a system for monitoring risks associated with drug and biologic products using data from disparate sources. The Sentinel System has completed hundreds of analyses, including many that have directly informed regulatory decisions. The Sentinel System also was designed to support a national infrastructure for a learning health system. Sentinel governance and guiding principles were designed to facilitate Sentinel's role as a national resource. The Sentinel System infrastructure now supports multiple non-FDA projects for stakeholders ranging from regulated industry to other federal agencies, international regulators, and academics. The Sentinel System is a working example of a learning health system that is expanding with the potential to create a global learning health system that can support medical product safety assessments and other research.